Nurse Caring Behavior in Increasing Patient Satisfaction - Nova Nurwinda Sari; Annisa Agatha; Septi Kurniasari (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
In an effort to accelerate the improvement of public health status, a strategic role is needed from health services that must be able to provide quality services according to the needs and desires of patients. The quality of nursing services is reflected in the implementation of professional nursing care which is a combination of intellectual, technical and interpersonal knowledge and skills which in practice reflects caring behavior. The purpose of this study was to determine the relationship between nurse caring behavior and patient satisfaction at the Padang Ratu Health Center, Central Lampung Regency. This type of research is quantitative, analytical design, cross sectional approach. The population in this study were all inpatients at the Padang Ratu Health Center, Central Lampung Regency, for the period January-March, with a total of 180 people. The sampling technique used was accidental sampling with a total sample of 125 respondents. The results of the bivariate analysis obtained p-value 0.037 (p-value < 0.05), which means that there is a relationship between nurse caring behavior and patient satisfaction at the Padang Ratu Health Center, Central Lampung Regency. Nurses' caring behavior must continue to be fostered by nurses in providing nursing care to patients. Nurses need to be continuously motivated in implement and improve caring behavior, because caring behavior not only determines the quality of service but can also affect the patient's ability to recover.